Phosphorus deficiency stimulates dominance of Cylindrospermopsis through facilitating cylindrospermopsin-induced alkaline phosphatase secretion: Integrating field and laboratory-based evidences. (1st December 2021) - Lu, Zhe; Lei, Lamei; Lu, Yan; Peng, Liang; Han, Boping
Abstract: Potentially toxic Cylindrospermopsis raciborskii blooms are of emerging concerns, as its scale is spreading from tropical regions to high latitudes, increasing the risk of aquatic biota being exposed to cylindrospermopsin (CYN). So far, CYN-producing C. raciborskii strains have only been reported in tropical waters which are commonly phosphorus (P)-deficient, where they can dominate phytoplankton communities. However, the influence of CYN on phytoplankton communities under different P status remains unclear. In this study, we first analyzed the summer observations of 120 tropical reservoirs in Guangdong Province. The proportion of potential CYN-producers was significantly higher in P-deficient and CYN-present reservoirs than that in P-sufficient or CYN-absent ones. This suggested that in P-deficient condition, the potential CYN producers might gain more advantages by the help of CYN. Then, in laboratory experiments we found that upon P deprivation, CYN did not inhibit the cell growth of other algal cells, but significantly stimulates them to secret more alkaline phosphatase (ALP) than in P-sufficient condition. Through transcriptomics, we further revealed that under such P-deficient condition, CYN remarkably induced intracellular nitrogen allocation and protein export system by activating the PIK3/Akt-cGMP/PKG signaling pathways in Scenedesmus bijugatus, thus enhancing its ALP secretion. Our study implies that CYN-induced ALP secretion is facilitated upon P deficiency, thus supporting the dominance of its producers C. raciborskii . Graphical abstract: Image 1 Highlights: Potential CYN-producer gain more advantage in P-deficient CYN-present reservoirs. P deficiency enhanced the CYN-induced ALP secretion. CYN did not inhibit the growth of three algal cells irrespective of P status. CYN could trigger the growth of P-sufficient chlorophytes. CYN activated N allocation and protein export to induce ALP secretion.